La Estambul de Orhan Pamuk - Sabugo, Mario S. (2008)
Comentarios sobre el libro "Estambul. Ciudad y recuerdos" del literato turco.
Keywords: URBANISMO; ARQUITECTURA; CIUDADES; LIBROS; LITERATURA; ESTAMBUL; MARMARA; TURQUIA